Effects of thermal and hurdle treatment on the stability of winter melon puree / Wan Saidatul Syida Wan Kamarudin - Wan Kamarudin, Wan Saidatul Syida (2014)
Winter melon is normally consumed in fresh form as it is easily perishable upon storage.Hence, this study was conducted with the aimed to increase the shelf life of this fruit by processing into canned purees. Two treatment methods were conducted on the samples namely thermal treatment and hurdle treatment. Results from the phytochemical screening showed the presence of three phytochemicals in the WMP. Three phenolic acids were also identified by using. In physical and chemical analysis, hurdle treated (HT) WMP were found to improve the physical properties and retain the bioactive component.Sensory evaluation by quantitative descriptive analysis (QDA) showed that HT WMP was most preferred by panelist. The next stage of study was conducted on the shelf life of canned WMP samples stored at different temperatures (25°C, 5°C and -20°C) for 6 months. A gradual decreased in ascorbic acid content (AAC) and total phenolic content (TPC) were observed throughout 6 months of storage period. Antioxidant activity (AOA) of all treated purees experienced reduction especially purees stored at room temperature and higher losses were observed in DPPH and FRAP assays. Physicochemical analysis showed that both treatments resulted in decreasing pH, increasing in awand decreasing in L* but maintaining the a* and b* of WMP colour. All treated WMP count for mold and yeast and total plate count growth were within the acceptable limit « 5 log CFU/ml). The sensory evaluation showed that HT WMP were more preferred by panelists compared to TT WMP. Hence, by using HT, it is possible to improve not only the microbial stability but also the sensory quality of the puree.